Adherence to European Society for Cataract and Refractive Surgery Recommendations among Italian Cataract Surgeons: A Survey. Issue 5 (September 2016) - Grosso, Andrea; Pertile, Grazia; Marchini, Giorgio; Scarpa, Giuseppe; Ceruti, Piero; Prigione, Guido; Romano, Mario R.; Bert, Fabrizio; Gili, Renata; Panico, Claudio; Siliquini, Roberta; Engelbert, Michael
Purpose: To survey the surgical routines with regards to prophylactic strategies in a sample of Italian hospitals and compare these with European Society for Cataract and Refractive Surgery (ESCRS) guidelines. Methods: Six private and 18 public hospitals were included in this clinical-based retrospective study. The overall volume of cataract operations in the 24 centers in 2013 was 43, 553. Main outcome measure was incidence of endophthalmitis per 1, 000. An incidence of less than 0.13% was considered acceptable. Results: Our study provides the first Italian data on the use of intracameral antibiotics in cataract surgery as recommended by the ESCRS. Thirteen centers (54%) used intracameral cefuroxime at the end of surgery. Of the 13 centers that used cefuroxime, 8 (62%) had an incidence of endophthalmitis less than 0.13%. Of the 7 (29%) centers that did not use intracameral cefuroxime, all had an endophthalmitis rate of greater than 0.13%. This difference was statistically significant (p<0.05). Among the 4 centers not included, 2 used vancomycin in the infusion bottle, 1 a fluoroquinolone, and the last a combination of antibiotics. The majority of surgeons (71%) used preoperative antibiotic eyedrops, but this measure was not shown to be significantly protective. Conclusions: Slightly more than half of the centers surveyed in this study adhered to the recommendations of the ESCRS and routinely employed prophylactic intracameral cefuroxime. An incidence of endophthalmitis greater than 0.13% was encountered significantly more frequently among centers that did not employ intracameral cefuroxime.